The Definition and Measurement of Poverty: An Integrated Islamic Approach (The Pakistan Development Review, 1997)
In this paper an attempt is made to learn as to how the Islamic shariah defines and measures the phenomenon of poverty. A systematic study of the Qur’an, the traditions of Holy Prophet Muhammad (peace be upon him), the conduct of righteous caliphs, and the writings of early Muslim jurists would make it clear that the poor, indigent, and destitute are given adequate importance. The early Islamic state, where necessary, made serious efforts to assist and rehabilitate the poor and the needy. One of the means of assistance and rehabilitation was zakat. The disbursement of zakat funds required that the poor should be unambiguously and convincingly separated from the non-poor. How was it done in the past? Traditions of the Prophet (the sunnah) throw sufficient light on this issue. When we carefully go through the traditions, it would be clear that the explanation of poverty as given by the Prophet is dynamic. It defies time and space limitations. A deeper probe of the traditions would reveal that, for all practical purposes, the Prophet has stressed on an integrated approach. His explanation is far more comprehensive, integrated, and meaningful than the one expressed today in terms of daily intake of certain minimum calories. Present-day Muslim countries should redefine their approach towards the definition and measurement of poverty to reflect the essence of Islamic shariah.